Práticas de leitura de estudantes do curso de pedagogia: entre apropriações e formalidades - Silva, Aline Ramiro da [UNESP] (2015)
This research aims to map, above all, the prevailing practices of reading in students of Pedagogy in a public university located in the state of São Paulo, comparing them with the analytical literature in the school culture in order to understand how it occurs, by analyzing such practices, the appropriation of professional knowledge by graduate students. Thus, the relationship between the perspective of school culture and cultural practices is based on the propositions of the authors Antonio Viñao Frago, Agustín Escolano Benito, Daniel Roche, José Mario Pires Azanha, Michel De Certeau, Pierre Bourdieu, Roger Chartier, among others. For the development work, as well as documentary research a mapping was conducted from quantitative data that the Foundation which conducts public contests and entrance tests for the universities answered by four hundred students. The period covers the years between 2010 and 2013, quantitative data obtained through the construction and application of questionnaire on cultural practices answered by three hundred and fifteen students of the Faculty of Education, with questions about cultural consumption. Finally, from the qualitative data obtained through semi-structured interview about the personal reading practices applied to twenty-four students. It is important to highlight that both the preparation of the questionnaire the construction of the interview relies mainly on the contributions of Pierre Bourdieu and Daniel Roche. Regarding triangulation and analysis it is intended to operationalize the concepts of tactic, strategy, formality and ownership practices, developed by Michel de Certeau as well as consider the very rich proposals of Roger Chartier about reading. It is important to state that this work is part of FAPESP research titled Cultural practices and teacher training: a study on (the) Faculty of Education students, coordinated by teacher Vera Teresa Valdemarin